Next-Generation Satellite Remote Sensing: Innovations, Applications, and Future Prospects - V Hans (International Journal of Satellite Remote Sensing, 2025)
Advances in satellite remote sensing have revolutionized our ability to monitor, analyze, and understand the Earth's environment across various scales. Over the past few decades, the field has seen remarkable progress in sensor technology, data processing techniques, and analytical methodologies. Modern satellites now provide high-resolution imagery and multi-spectral data, enabling enhanced monitoring of land cover, atmospheric conditions, oceanic dynamics, and natural disasters. These advancements have facilitated improvements in climate change modeling, resource management, urban planning, and disaster response. Furthermore, the integration of machine learning and artificial intelligence has significantly boosted the accuracy and efficiency of data interpretation, fostering innovative applications in environmental monitoring and forecasting. This article explores the latest trends in satellite remote sensing, focusing on new technologies, data acquisition systems, and interdisciplinary applications, while also addressing challenges such as data privacy, accessibility, and the need for international collaboration in space-based observation efforts.
Keywords: cryosphere; range of applications; remote sensing; space-based observation efforts